Persediaan dan Teknik dalam Perencanaan Sumber Daya Manusia Yang Berkualitas - Agisti Maharani; Selvina Pratama; Esterrita Manalu; Yusawinur Barella (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2024)
Human resources are the workforce needed in every organization and country because this workforce is a driving force in the sustainability of an organization, company and country. Inventory in the procurement of human resources in this context is related to procurement which refers to the amount of availability and characteristics of qualified workforce owned by an organization or country to meet the needs of the organization or country in achieving certain goals. This technique in quality human resource planning is related to the steps in the approach, methods and processes carried out by the organization to ensure that the organization gets a workforce that suits the needs and goals of the organization. Human resource planning refers to an activity or activity carried out by the organization in an orderly manner that is related to preparing future workforce needs by using resources that are appropriate to needs and of good quality.